Papilomatosis in dogs: Literature review and study of twelve cases - Fernandes, Marta Catarina [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Fedato, Fabiana Pólis; Paes, Antonio Carlos [UNESP]; Megid, Jane [UNESP] (Universidade Estadual de Londrina, 2009)
Canine papillomatosis is an infectious viral disease characterized by oral, cutaneous or ocular papillomas, usually benign. The treatment is indicated in animals, with multiple tumors that produce pharyngeal obstruction, and problems of eating or for aesthetic reasons. Different treatment protocols have been proposed, including surgical excision, cryosurgery, electro surgery, autogenous or recombinant vaccines, imunomodulators drugs, systemic and intralesional chemotherapy. In this study were reviewed the more important aspects of canine oral papillomatosis. In the 12 studied animals, the papillomas were observed predominantly in mouth, gum and palate regions, in puppies until 12 months, presenting combined infection with ehrlichiosis. The treatment using Propionibacterium acnes and/or autogenous vaccine showed efficacy in eight dogs (66.7%).
Papilomatose oral em cães: revisão da literatura e estudo de doze casos
Keywords: Clinic; Dog; Epidemiology; Papillomavirus; Papilomatosis; Therapy